Energy, economic and environmental performance assessment of a grid-tied rooftop system in different cities of India based on 3E analysis - Saxena, Anupama Khare; Saxena, Seema; Sudhakar, K. (Oxford University Press, 2021)
India is very rich in solar energy, with a total of 3000 sunshine hours annually in most places. The installation of on-grid rooftop electricity-generation photovoltaic (PV) systems is currently undergoing substantial growth and extension as an alternate source of energy that contributes to Indian buildings. This paper analyses the viability of mounting solar PV plants in distinct cities of India in various locations with different climate conditions such as Delhi, Bhopal, Udaipur, Ahmadabad, Thiruvananthapuram, Pune and Madurai. The technical feasibility of installing a 100-kWp system is evaluated using PVsyst software under local climatic conditions. The performance ratio is between 70% and 80%, with a capacity utilization factor of 19–21% and estimated energy output of 170 MWh annually at all sites. The system produces 400–500 kWh of energy daily at a per-unit cost of INR 6–7 (Indian rupees) in all locations. The lifespan of the system is ~25–30 years, reducing about 150–170 tons of carbon-dioxide emission to the atmosphere every year. The payback period of the system is ~5–6 years, which defines its feasibility. This information would encourage organizations and individuals to install such PV plants on the rooftops of buildings to use solar electricity for meeting the energy demands of the country.